2022
DOI: 10.6007/ijarbss/v12-i4/13035
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Sharia Fintech Among Millenial in Indonesia: Moderating Effect of Islamic Financial Literacy on UTAUT 2

Abstract: The development of Islamic Fintech in Indonesia shows promising progress. As of April 2021, there are 146 fintech companies. However, this large number of companies is only able to reach 7% of the total population in Indonesia. This study aims to examine what factors that influence the intention to use Islamic fintech in Indonesia by testing the UTAUT 2 theory developed by Venkatesh with the addition of Islamic Financial Literacy as a moderating variable. Data was collected through an online questionnaire adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
3
14
1
1
Order By: Relevance
“…Initially, Venkatesh et al (2003) in UTAUT 1 proposed that facilitating condition does not have a direct impact on behavioral intention but instead affects actual user behavior which later in UTAUT 2 found that facilitating condition has a strong influence on behavioral intention (Venkatesh et al, 2012). Moreover, prior studies have shown that facilitating condition is strongly related to users' behavioral intentions (Shaw, 2015;Basri, 2018;Merhi et al, 2021;Xie et al, 2021;Mansyur and Engku Ali, 2022;Rahim et al, 2022). Therefore, considering the above discussion, we hypothesize: H4.…”
Section: Facilitating Conditionsmentioning
confidence: 90%
See 3 more Smart Citations
“…Initially, Venkatesh et al (2003) in UTAUT 1 proposed that facilitating condition does not have a direct impact on behavioral intention but instead affects actual user behavior which later in UTAUT 2 found that facilitating condition has a strong influence on behavioral intention (Venkatesh et al, 2012). Moreover, prior studies have shown that facilitating condition is strongly related to users' behavioral intentions (Shaw, 2015;Basri, 2018;Merhi et al, 2021;Xie et al, 2021;Mansyur and Engku Ali, 2022;Rahim et al, 2022). Therefore, considering the above discussion, we hypothesize: H4.…”
Section: Facilitating Conditionsmentioning
confidence: 90%
“…According to Yan et al (2021), consumers tend to use the technology that facilitates them to attain their goals. It is the ease of use of the system, which consequently reduces the time and effort devoted while doing a task (Mansyur and Engku Ali, 2022). However, it mostly affects users' intent initially, while using a technology later, it becomes less crucial as this procedure is substituted by the efficiency of the technology (Rahim et al, 2022).…”
Section: Customer Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ajzen defines perceived behaviour control as the perceived ease or difficulty of carrying out a behaviour based on previous experiences, problems, and preparation of such difficulties (Ajzen, 2005). The availability of financing, details, and facilities used to support investment activities on the Equity Crowdfunding platform is defined as convenience and problems in the context of this research (Mansyur & Ali, 2022). Supporting factors play an essential role in controlling behaviour and vice versa, so if the supporting instrument is hard to fulfil, the more difficult it is to understand a person's behaviour (Ajzen, 2005).…”
Section: Fig 1 the Theory Of Planned Behaviourmentioning
confidence: 99%